A thermodynamics-based hyperelastic-plastic coupled model unified for unbonded and bonded soils. (February 2021) - Zhang, Zhichao; Li, Linhang; Xu, Zhenglong
Abstract: A hyperelastic-plastic coupled constitutive model unified for bonded and unbonded soils is developed in this paper based on thermodynamics. An elastic potential function applicable for different kinds of soils is proposed to derive a hyperelastic model accounting for the pressure- and -density dependency, the stress-induced anisotropy and the bonding effects as well as their couplings with plasticity. From the perspective of elastic stability, state boundary and failure surfaces of different soils can be naturally predicted by the hyperelasticity without any additional definitions and parameters. Based on the classical nonequilibrium thermodynamics, novel plastic constitutive relations are derived and naturally coupled with the hyperelasticity. As a result, elasto-plastic coupling features such as the dissipative history effect on elastic stiffness, the cyclic shear behavior, the degradation of shear modulus under small strain conditions, the stress-induced anisotropy of plastic behavior and the cohesion degradation can be reproduced. The model is well validated by predicting the undrained/drained monotonic and cyclic shear behavior of unbonded and bonded sands, providing useful insights into their critical state behavior, irreversible shear-dilation/contraction and effects of bonding and cohesion degradation. It is also shown that the cohesion degradation in different shearing stages to a large extent determines both the monotonic and cyclic behavior of bonded soils. Highlights: A thermodynamic hyperelastic-plastic coupled model is derived for saturated soils. Bonding and cohesion degradation count in both energy potentials and dissipations. The theory naturally predicts the stress-induced anisotropy of stiffness and strength. Elasticity and plasticity are coupled with each other without concept of yield surface. The theory gives insights into critical state and cyclic behavior of various soils.